Does Anybody Still Need Judaism? - Gordon, Daniel (History and theory, 2018)
Both of the books under review focus on the tradition of Jewish scholarship and debate. The Genius of Judaism is written from a religious perspective, whereas the authors of Jews and Words envision a future in which Jews live without Judaism; they see Jewishness as a culture that can be divorced from religion. For Lévy, a sense of the divine—including the concept of being a chosen people—is the source of Jewish identity and historical continuity. Lévy also argues that the Jews are chosen to serve non-Jews. Inspired by the prophet Jonah, Lévy undertook diplomatic missions in the Ukraine and in Libya, and I consider the lessons he draws from these missions. I also discuss the relationship of Judaism to various concepts in the philosophy of history: revolution, progress, messianism, and utopianism, as well as the affinity between Judaism and skepticism.